Charitable giving behavior in northeast thailand and mukdaharn province: Multivariate tobit models - Jintanee Jintranun (2018)
As an Asian and Buddhist nation, Thailand's population is particularly concerned with charitable giving, and does so through several channels. This paper quantifies charitable donations for the poorest region of Thailand (the Northeast) and compares the shares of a household's charitable donation expenditures of three types with those allocated to religion-consistent food and religion-antipathetic alcohol consumption. It also tests for significant differences by degree of modernization (GPP/capita) and proximity to a major highway. We employed dataset collected by the National Statistical Office on nineteen Northeastern provinces, including 11,850 observations.The objective was to estimate multivariate tobit models and compare expenditure behavior under Engel's law. The analytical results reveal that the share of religious institutional donations, like the share of food, declines with income (Engel-negative); while alcohol expenditure, direct donations to NGOs display a positive relationship with household income (Engel-positive). Moreover, households located within poorer-than-average Mukdaharn province and along the East-West Economic Corridor province have a higher share of religious institutional donations than otherwise. Other demographic determinants of charitable giving include education level, the characteristics of the household head, and work status. If charitable donations by individuals to individuals (direct donation) increased by 60 percent of their current value, they would be adequate to eradicate poverty without recourse to governmental or NGO programs. Policy suggestions are made in this direction. © 2013 Springer-Verlag Berlin Heidelberg.